Prevalence and Clinical Characteristics of Human Hepatic Capillariasis in Asia: Review - Choirunnisa, Indaka Rachmah; Suwanti, Lucia Tri; Mufasirin; Puspitasari, Heni (Universitas Airlangga, 2026)
Human hepatic capillariasis in Asia is likely under-detected rather than rare. This review aimed to synthesize prevalence signals and describe clinical characteristics of hepatic capillariasis caused by Calodium (Capillaria) hepatica across Asian countries. A systematic search of major databases through 2025 identified case reports, case series, and hospital-based studies on human hepatic capillariasis. We extracted data on study design and diagnostic approaches, including histopathology, imaging, and molecular assays such as 18S rRNA sequencing. Clinical outcomes were recorded separately. Evidence was sparse and geographically clustered, with 20 publications from 7 countries concentrated in East and Southeast Asia. Most reports described single patients or small series. Clinical presentations commonly included hepatic mass-like lesions and eosinophilia, and misdiagnosis as neoplasia or other hepatobiliary disease was frequent. Histopathology was the primary diagnostic tool. Molecular confirmation was applied inconsistently, but, when used, enabled species-level identification. Because of heterogeneity in diagnostics (microscopy, histopathology, PCR), study populations (single cases vs hospital series), and locations (sites across East and Southeast Asia), and because denominators were small, we did not calculate a pooled prevalence. Nevertheless, high carriage rates in urban rodent reservoirs suggest under-recognition in humans. As part of integrated One Health surveillance, this review highlights the need to integrate histopathology with molecular testing, adopt standardized reporting that distinguishes genuine infections from spurious findings, and strengthen cross-sector collaborations to refine burden estimates and guide prevention across Asia.